Mis-education, Translation and the Barkada of Languages: Reading Renato Constantino with Nick Joaquin - Rafael, Vicente L. (Archīum Ateneo, 2024)
This paper re-visits the classic piece by Renato Constantino, “The Mis-education of the Filipino” (1959/1966), inquiring into the colonial basis of his anti-colonial critique of American English. It explores the affinity between his view of language and those of American colonial officials, especially around the relationship between English and the vernacular languages. Both conceived of that relationship in terms of a war of and on translation. It then turns to an important but overlooked essay by Nick Joaquin published around the same time as Constantino’s, “The Language of the Streets” (1963). By closely considering Joaquin’s views on “Tagalog slang” as the basis for a national language, we can see a different politics of language at work, one based not on translation as war but as play. Whereas Constantino was concerned with language as the medium for revealing the historical truth of nationhood that would lead to democratizing society, Joaquin was more interested in the conversion of history into language as a way of expanding literary democracy.